(untitled) (Perner’s Contacts, 2017)
The aim of the article is to experimentally evaluate the contact area and to compare the measured results with different contact model theories. The experiment takes advantage of the electrical contact resistivity principle in a dry piston/cylinder liner test rig assembly. Analytical contact models are implemented into the computational simulation. The calculated contact area depends on the dynamics and precomputed database of contact pressure and contact area in relation to the separation distance of surfaces.